2000
DOI: 10.1159/000022933
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Transmission Probabilities in Families Ascertained through a Proband with Variable Age-at-Onset Disease: Application to the HLA A, B and DR Loci in Finnish Families with Type 1 Diabetes

Abstract: An open problem of some interest in the study of HLA has been the possible existence of transmission distortion in the human HLA complex. In this paper, transmission probabilities are estimated and tested using data on HLA A, B and DR loci genotypes of parents and offspring ascertained from the entire population of Finland (Childhood Diabetes in Finland Study) through one or more offspring diagnosed with insulin-dependent diabetes mellitus (IDDM) during the recruitment period from September 1986 to July 1989. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…Studies over the last decades have reported linkage and/or associations of T1DM with HLA in both class I and II alleles, but no single locus or allele can explain observations in risk of T1DM [7][8]. In a previous study [9], we could not find any evidence of non-Mendelian transmission of HLA candidate genes in the Finnish population explaining even partially the observed increase in incidence of type 1 diabetes in Finland. A systematic evaluation of the joint risk of HLA A, B and DR loci and their haplotypes by Thomas et al [10] supported DR locus as a major contributor, and found some evidence of three-locus haplotype effects in the risk of T1DM.…”
Section: Introductioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Studies over the last decades have reported linkage and/or associations of T1DM with HLA in both class I and II alleles, but no single locus or allele can explain observations in risk of T1DM [7][8]. In a previous study [9], we could not find any evidence of non-Mendelian transmission of HLA candidate genes in the Finnish population explaining even partially the observed increase in incidence of type 1 diabetes in Finland. A systematic evaluation of the joint risk of HLA A, B and DR loci and their haplotypes by Thomas et al [10] supported DR locus as a major contributor, and found some evidence of three-locus haplotype effects in the risk of T1DM.…”
Section: Introductioncontrasting
confidence: 63%
“…According to Pitkäniemi et al [9] subjects who are not eligible as probands (E ij = 0 i.e. born prior to c 0 -w and those born after the proband) j1 contribute to the above This means that given subject is proband he/she is also susceptible and non-susceptible subject can not be a proband.…”
Section: Long-term Survival Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not apply any available statistical methods for possible correction of ascertainment problem because either conditional likelihood methods are developed for different phenotypes than variable age at onset [Burton, 2003] or they are not directly applicable to the variable age-at-onset disease with population (registry)-based recruitment . Ascertainment correction for population-based T1D registry data with variable age at onset by Pitkaniemi et al [2000] lead to substantial loss of data and thus the analysis would suffer from insufficient power. There are also interesting proposals to use computer intensive methods [Burton, 2003;Clayton, 2003] or recently proposed different forms of conditional likelihoods [Ginsburg et al, 2003;Carayol and Bonaiti-Pellie, 2004].…”
Section: Discussionmentioning
confidence: 99%
“…Such an extreme form of transmission distortion seems biologically and empirically [35] very unlikely, given current knowledge of Type 1 diabetes genes and their effects. Therefore, it is evident that biologically reasonable transmission distortion alone, with penetrances as defined for example DR4 carrier and non-carrier genotypes, can explain only a small part of the rapid increase in the incidence of Type 1 diabetes observed in Finland.…”
Section: Discussionmentioning
confidence: 99%